Evaluation of omentin levels in patients with unstable angina pectoris, non-ST elevated myocardial infarction (NSTEMI) and STEMI - Akbulut, Tayyar; Asoğlu, Ramazan; Özdemir, Mahmut; Aladağ, Nesim; Karauzum, İrem and Şipal, Abdulcebbar and Karaüzüm, Kurtuluş (Journal of Surgery and Medicine, 2020)
Aim: Acute coronary syndrome (ACS) is an ischemic cardiac disease that could result in myocardial necrosis with prolonged ischemia. Omentin (intelectin-1) is a new biomarker that is released from adipose tissue. It is associated with coronary artery disease (CAD) and has an acute ischemic injury-reducing effect. This study aimed to assess the omentin levels in patients with unstable angina pectoris (USAP), Non-ST segment elevation myocardial infarction (NSTEMI), and ST-segment elevated myocardial infarction (STEMI). Methods: This case-control prospective study included 59 patients with ACS and 22 healthy subjects. MB fraction of creatine kinase (CKMB), troponin, myoglobin, and omentin levels were measured from venous blood obtained from each patient within six hours after the onset of symptoms. Plasma omentin levels were determined with an omentin enzyme-linked immunosorbent assay kit. Results: The patient group was older than the control group (P<0.05) but there was no difference between the groups in terms of gender (P>0.05). The rate of smoking was higher in the patient group, and the patient group was heavier than the control group (P>0.05). Omentin levels were similar in ACS patients and control subjects (6.0 (1.7) vs. 6.3 (1.3), P=0.40). There was no significant correlation among CKMB, troponin, myoglobin, and omentin levels. Moreover, omentin levels were similar in ACS subgroups (P=0.58). There was no significant correlation between body mass index and omentin levels (r =-0.186, P=0.09). Conclusion: This study revealed that there was no significant relationship between omentin and myoglobin levels in ACS patients. The potential usefulness of blood concentrations of omentin levels in understanding the relationship with ACS warrants further studies.